(untitled) (Contemporary Journal of Social Science Review, 2025)
Purpose – This study examines whether perceived AI‑supported autonomy (PAISA) directly influences employee exploration, intention to use AI, AI trust, and AI adoption. Methodology – A survey of 410 employees in Pakistan was analyzed using structural equation modeling to test four direct hypotheses. Findings – PAISA significantly and positively affects exploration (β = 0.412), intention (β = 0.271), trust (β = 0.338), and adoption (β = 0.198). All effects are significant at p < 0.001. Practical implications – Organizations should design autonomy‑enhancing AI systems and encourage hands‑on experimentation to boost adoption. Originality/value – First study to test the direct effects of PAISA on all four outcomes simultaneously, and first in the Pakistani context.